The cost-effectiveness of point of care testing in a general practice setting: results from a randomised controlled trial - Briggs Nancy E; Moss John R; Laurence Caroline O; Beilby Justin J (BMC, 2010)
Abstract Background While point of care testing (PoCT) for general practitioners is becoming increasingly popular, few studies have investigated whether it represents value for money. This study aims to assess the relative cost-effectiveness of PoCT in general practice (GP) compared to usual testing practice through a pathology laboratory. Methods A cost-effectiveness analysis based on a randomized controlled trial with 4,968 patients followed up for 18 months and fifty-three general practices in urban, rural and remote locations across three states in Australia. The incremental costs and health outcomes associated with a clinical strategy of PoCT for INR, HbA1c, lipids, and ACR were compared to those from pathology laboratory testing. Costs were expressed in year 2006 Australian dollars. Non-parametric bootstrapping was used to generate 95% confidence intervals. Results The point estimate of the total direct costs per patient to the health care sector for PoCT was less for ACR than for pathology laboratory testing, but greater for INR, HbA1c and Lipids, although none of these differences was statistically significant. PoCT led to significant cost savings to patients and their families. When uncertainty around the point estimates was taken into account, the incremental cost-effectiveness ratio (ICER) for PoCT was found to be unfavourable for INR, but somewhat favourable for ACR, while substantial uncertainty still surrounds PoCT for HbA1c and Lipids. Conclusions The decision whether to fund PoCT will depend on the price society is willing to pay for achievement of the non-standard intermediate outcome indicator. Trial registration Australian New Zealand Clinical Trial Registry ACTRN12605000272695